MODELAGEM AB INITIO DA CISTEÍNA ADSORVIDA EM GRAFENO - Dutra, Fabricio Andre (2010)
The graphene is a two-dimensional network composed of carbon atoms arranged in hexagonal rings; characterized as "thinner material of the universe", which exhibits high crystal quality and ballistic electrical transport at low temperatures. This material presents electronic properties and large surface area that are interesting to adsorb or substitut aminoacids, to increase the hydrophilicity of the structure originally constituted only of carbon atoms and then enable the development of new sensors with high molecular sensitivity. This work aim to evaluate the structural and electronic properties of the grapheme interacting with the aminoacid cysteine, and the type of interaction established between this and monolayer graphene perfect or structural defect. These properties are investigated through computer simulation from first principles methods using the density functional theory that indicate the electronic and structural properties of the resulting systems. We found that the binding energy between the amino and graphene monolayer varies, being totally dependent on the reaction site and among the three sites considered (carboxyl, amine and thiol), both, in considering the perfect layer of graphene or with as structural defect, present the thiol group with a stronger interaction. In the electronic properties, we demonstrate little interaction between the systems, because the levels of isolated systems appear clearly in the structures of interacting systems, which demonstrates the low binding energy found. Thus, this study demonstrated, the properties associated with the interaction of amino acids adsorbed on graphene encouraging potential technological application of this innovative material as a sensor of more complex molecules.